2020
DOI: 10.3390/s20072143
|View full text |Cite
|
Sign up to set email alerts
|

An Affordable Fabrication of a Zeolite-Based Capacitor for Gas Sensing

Abstract: The development of even more compact, inexpensive, and highly sensitive gas sensors is widespread, even though their performances are still limited and technological improvements are in continuous evolution. Zeolite is a class of material which has received particular attention in different applications due to its interesting adsorption/desorption capabilities. The behavior of a zeolite 4A modified capacitor has been investigated for the adsorption of nitrogen (N2), nitric oxide (NO) and 1,1-Difluoroethane (C2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…NO adsorption capability depends on several material characteristics, including the pore and the adsorbed molecule sizes, the cation nature, its distribution and concentration throughout the porous structure, the polarization and the quantity of water [10]. In Figure 1 are depicted the different inorganic porous materials selected for the NO-releasing assessment that had previously shown potential for NO storage [16][17][18][19].…”
Section: No Adsorption Capacity Of Different Porous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…NO adsorption capability depends on several material characteristics, including the pore and the adsorbed molecule sizes, the cation nature, its distribution and concentration throughout the porous structure, the polarization and the quantity of water [10]. In Figure 1 are depicted the different inorganic porous materials selected for the NO-releasing assessment that had previously shown potential for NO storage [16][17][18][19].…”
Section: No Adsorption Capacity Of Different Porous Materialsmentioning
confidence: 99%
“…Although a wide range of NO analytical methods exists, including highly sensitive gas sensors [10][11][12], only few can quantify the gas under liquid biological environments. Besides, their performances are strongly dependent on the NO-releasing scaffold type (e.g., macromolecular particles, films, gels, coatings, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolite is a microporous aluminosilicate with a peculiar crystalline structure, a specific Si/Al ratio, and a mobile metal cation, which confers stable chemical/physical characteristics [23][24][25]. One of the main characteristics of this porous material is its physical adsorption capability, which allows the trapping of specific molecules inside the crystalline framework in the liquid or gaseous phases [26][27][28][29]. Recent studies evidenced that zeolite is found in a wide range of environmental applications, such as reducing VOC levels, the removal of CO 2 from the environment, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites were suggested for sensor applications over two decades ago, e.g., References [ 34 , 35 ]. Since then, zeolites have been largely applied in gas sensors [ 36 ] (and references therein), whereas their applications for aqueous media are scarce. Their ion exchange property and the ability to withstand pressures needed to produce ISPs (4+ tonnes as shown in the original publication [ 33 ]) were the key driver of their application in ISPs.…”
Section: Introductionmentioning
confidence: 99%